Tanggung Jawab Penjual Atas Tindakan Wanprestasi Dalam Jual-Beli Diamond Game Online Mobile Legends - Pamungkas, Putra; Berlianty, Teng; Kuahaty, Sarah Selfina (Faculty of Law Universitas Pattimura, 2025)
The dimension of e-commerce in ITE Law Number 19 of 2016 and ITE Law Number 19 of 2016, which requires everyone to provide complete information and prohibits everyone from spreading fake news. In everyday life, what often occurs is default on consumers who like to play online games, especially Mobile legend. In reality, many defaults occurred but consumers did not have access to sue Top Up Store accounts because consumers had been blocked. Therefore, Mobile Legends players who feel aggrieved due to Top-Up diamonds and Top Up Store not repairing or refusing compensation can file a lawsuit to receive compensation. A clear dispute resolution process must exist in the event of a default. The research methods used are normative legal research or library legal research. The type of research used is analytical descriptive research. The research approach carried out by the researcher is the conceptual approach and the legislative approach (Statue Approach). Legal materials include primary legal materials, secondary legal materials, and tertiary legal materials. The results of the research conducted by the researcher concluded that, based on the Civil Code, the force of binding diamond purchase and sale agreements by sellers other than official providers, it is clearly explained that between buyers and unofficial providers, it is absolutely binding. This is because there is an element of agreement between the two parties. In addition, the ITE Law in Article 9 also guarantees binding force between non-official providers and consumers. This can be seen as evidence of communication related to diamond buying and selling transactions on Mobile Online Games. The form of responsibility in this case for the seller for the default of buying and selling Mobile Legends Diamonds through the Top Up Store can be resolved through the Consumer Dispute Resolution Agency (BPSK).